Management of Unresectable Metastatic Primitive Myxoid Mesenchymal Tumor of Infancy: A Case Report and Systematic Review of the Literature. Issue 3 (April 2020) - Asaftei, Sebastian D.; Campello, Anna; Tirtei, Elisa; Colombo, Sara; Vallero, Stefano; Boffano, Michele; Fagioli, Franca
Abstract : Primitive myxoid mesenchymal tumor of infancy is a rare soft tissue tumor. The present case is one of the most invasive primitive myxoid mesenchymal tumor of infancy reported to date. To our knowledge, it is the first case described with extensive involvement of pelvis and the third described developing metastasis and with an invasion of the spinal canal without evidence of transformation into undifferentiated sarcoma. The patient failed to respond to chemotherapy (CHT). According to the few available data, CHT seems to be more effective in the presence of metastatic disease or increased cellularity. However, CHT, including high-dose ifosfamide, resulted ineffective even after lung metastasis development with pathologic evidence of increased mitotic rate. The management of this case and the data in the literature confirm surgery as the gold standard treatment in this pathology.